SIAM CITRUS MARKETING ANNEXATION HISTORY IN SAMBAS - Sudrajat, Jajat (Paramita: Historical Studies Journal, 2018)
Ã‚Â Up to the present, the factors underlying the need for direct interventions from the government in Siam citrus market in Sambas regency still raise many questions. Therefore, this study is intended to analyze some moments in the dynamic history of Siam citrus farming and also to investigate some paradigms which affect them. This study used an agriculture development historical approach. This study found three periods in the dynamic history of Siam citrus farming in Sambas. They were marketing domination period by the middlemen during 1950s-1990, marketing domination period by the company during 1991- 1997, and recovery period from 2000 to present. Siam citrus farming achieved its prosperity and showed the sustainability aspect when it was organized by the middlemen. Unfortunately, this farming lost ground after its marketing was intervened directly by the government having appointed a private company as a marketing coordinator. This investigation also found at least three paradigms underlying the need for direct government intervention to regulate the Siam citrus market. They were the existence of a negative view (stereotypes) about middlemen, the drives to apply a core-satellite pattern in the marketing of agricultural products, and the spirit to develop cooperatives as a supporting institution of agricultural development.Hingga saat ini, faktor yang mendasari perlunya intervensi langsung pemerintah ke dalam pasar jeruk Siam di Kabupaten Sambas masih memunculkan banyak pertanyaan. Oleh karena itu, penelitian ini dimaksudkan untuk menganalisis beberapa momentum dalam dinamika sejarah usahatani jeruk Siam, dan juga menganalisis beberapa paradigma yang memengaruhinya. Penelitian ini menggunakan pendekatan sejarah pembangunan pertanian. Studi ini menemukan tiga tonggak dalam dinamika sejarah usahatani jeruk Siam di Sambas, yaitu periode penguasaan pemasaran oleh pedagang pengumpul: 1950an-1990, periode penguasaan pemasaran oleh perusahaan: 1991-1997, dan periode pemulihan: 2000-sekarang. Usahatani jeruk Siam mencapai kejayaan dan menunjukkan aspek keberlanjutan ketika diorganisir oleh pedagang pengumpul. Sayangnya, usahatani ini kemudian mengalami periode kehancuran setelah pemasarannya diintervensi langsung pemerintah dengan menunjuk perusahaan swasta sebagai koordinatornya. Penelaahan menemukan sekurang-kurangnya ada tiga paradigma yang mendasari perlunya intervensi langsung pemerintah mengatur pemasaran jeruk Siam, yaitu adanya pandangan negatif terhadap pedagang pengumpul, terdorong untuk menerapkan pola inti-plasma dalam pemasaran hasil pertanian, dan semangat menjadikan koperasi sebagai lembaga pendukung pembangunan pertanian.Ã‚Â Ã‚Â